Neurophenomenology of Savant Syndrome - Anurogo, Dito; Ikrar, Taruna (PT. Kalbe Farma Tbk., 2015)
Savant syndrome is an enigmatic disorder. It is characterized by cluster of outstanding mental ability in otherwise handicapped individuals. People with savant syndrome exhibit exceptional-extraordinary abilities and demonstrate some specific talents or particular skills along with developmental disabilities. Their profound and prodigous abilities are far in excess of what are considered normal. There is a paradoxical presence of special skills and distinguished disabilities. The documented savant skills include â€œlightning-speedâ€ numerical calculation, calendrical calculation, musical savants (exceptional musical abilities, especially perfect pitch), artistic skills, hyperlexics (fast reading and understanding). Other types of talents and artistic skills involving three-dimensional drawing, map memory, poetry, painting, and sculpturing are also observed. The goal of this scientific article is to review savant syndrome, based on neurophenomenology framework and recent findings.Sindrom savant adalah gangguan yang misterius. Sindrom ini ditandai dengan adanya beberapa kemampuan mental yang menonjol pada individu dengan kelainan/cacat jasmani. Orang dengan sindrom savant menunjukkan beragam kemampuan luar-biasa serta memiliki beberapa bakat khusus atau keterampilan yang istimewa di samping gangguan perkembangan. Kemampuan yang dimilikinya melampaui kondisi normal. Ada paradoks dari kehebatan dan cacat yang dimilikinya. Beberapa keterampilan yang terdokumentasikan, misalnya: perhitungan numerik kilat, kalkulasi kalender, musik (kecuali kemampuan musikal, terutama pitch yang sempurna), keterampilan artistik, hiperleksia (kemampuan membaca dan memahami kilat). Jenis bakat dan kemampuan artistik lainnya antara lain menggambar tiga dimensi, ingatan tentang peta, puisi, lukisan, dan seni memahat. Tujuan artikel ilmiah ini adalah untuk meninjau sindrom savant berdasarkan pendekatan neurofenomenologi, dan kepustakaan serta riset terkini.